Bismuth-rich bismuth oxyhalides for environmental and energy photocatalysis - Jin, Xiaoli; Ye, Liqun; Xie, Haiquan; Chen, Gang (Coordination chemistry reviews, 2017)
Bismuth-rich bismuth oxyhalides were used for photocatalytic solar fuel generation and environmental purification. [Display omitted] •Bismuth-rich bismuth oxyhalides for photocatalysis.•Bismuth oxyhalides for photocatalytic solar fuel generation.•Bismuth oxyhalides for photocatalytic environmental purification. Compared to bismuth oxyhalides (BiOX; X=Cl, Br and I), bismuth-rich bismuth oxyhalides (BixOyXz; X=Cl, Br and I) possess higher stabilization and more suitable band structure for photocatalysis. As a new type of photocatalyst, BixOyXz exhibit excellent photocatalytic properties for environmental purification (e.g. pollutant degradation), generation of solar fuels, production of hydrogen from water, CO2 conversion, nitrogen fixation and organic synthesis. The purpose of this review is to provide a concise summary on bismuth oxyhalides, including synthesis, modification and photocatalytic application of BixOyXz photocatalysts. We also offer insight into future research trends and developments including potential applications for BixOyXz photocatalysts.